Opinion on Legal Entity – Sustainability Nexus - (:unkn) unknown (My University, 2020)
The persons capable of exercising legal rights are not only human beings. Aside from the real persons, there are societies and institutions that could also be right holders. We could hear every day about a Municipality starting up a construction transaction, a club making a contract with a football player, a University reaching to a decision, a Foundation awarding a scholarship. The main reason for the establishment of such organizations is the limited life period of a human being. The shortness of lifespan is an impediment in reaching some goals that will necessitate longer time periods. Followingly people unite or gather their assets in order to maintain such goals that exceed the life period of human beings as associations and foundations . As a result, legal systems acknowledge legal personality to others besides human beings and this serves maintaining sustainability.

Hukuki açıdan haklara sahip olan ve haklardan yararlanma yetkisi bulunanlar, sadece gerçek kişiler değildir. Gerçek kişilerin yanısıra dernekler, vakıflar ve tüzel kişiliği bulunan şirketler gibi hak ve fiil ehliyeti olan tüzel kişiler mevcuttur. Gerçekten de her gün bir belediyenin inşaat sözleşmesi kurduğunu, bir spor kulübünün bir futbolcu ile sözleşme imzaladığını, bir üniversitenin bir karar aldığını veya bir vakfın öğrencilere burs verdiğini duyarız. Bu tip kurumların meydana getirilmesinin arka planında, insan yaşamının süresinin sınırlılığı olgusu yatar. Yaşamın kısa olduğu gerçeği, daha uzun zaman aralıklarına ihtiyaç gösteren amaçlara ulaşılmasında bir engel olarak ortaya çıkar. Bu sebeple, insan ömrünü aşan amaçları gerçekleştirebilmek için gerçek kişiler ya da malvarlıkları; dernekler, vakıflar, şirketler gibi tüzel kişilikler altında örgütlenmektedirler. Kısacası, hukuk sistemleri gerçek kişiler yanında diğerlerine de tüzel kişilik tanımak suretiyle, sürdürülebilirlik kavramına destek sağlamaktadırlar.
Tüzel Kişilik ve Sürdürülebilirlik İlişkisine Bir Yorum